'No Viral No Justice' Phenomenon in Indonesian Law Enforcement: Acceleration or Threat to Justice ? - Wahid, Abdul; Rohadi, Rohadi; Kusyandi, Andi (Reformasi Hukum, 2025)
The phenomenon of 'No Viral, No Justice' illustrates a shift in the paradigm of law enforcement in the digital age. Virality on social media is often a determining factor in driving the response of law enforcement officials. This study examines the role of social media virality in shaping public access to justice in Indonesia, known as the 'No Viral, No Justice' phenomenon. Using a socio-legal approach, this study analyzes the dynamics between digital public pressure and the response of law enforcement agencies in a number of cases that went viral. The results show that virality can accelerate the state's response in handling a case and open space for public participation. However, this phenomenon also has the potential to undermine fundamental principles in the judicial system, particularly the principle of due process of law, and create disparities in the handling of viral and non-viral cases. This study recommends the importance of formulating a regulatory framework that balances public participation through digital media as a tool for social control with the protection of the integrity, independence, and objectivity of the legal system. In conclusion, justice is not solely determined by media exposure but by the upholding of a legal system that ensures certainty, substantive justice, and the protection of the human rights of every citizen.